(untitled) (Ameghiniana, 2014)
Two new fossil species of terrestrial gastropods, Megaloouíímus unchmanni n. sp. and Strophocheilus groeberi n. sp., are described from Miocene tuffaceous deposits of the Limay river area, Río Negro province, Argentina. They represent the first record of Miocene Strophocheilidae from northern Patagonia. The likely biogeographical-evolutionary significance of this finding is also considered, framed into a vicariance scenario related to the Andean orogeny. The spatial proximity and rather generalized shell features observed may suggest a presumable origin for Chiliborus on the western slope of the Andes as consequence of mountain uplift and early isolation of a peripheral stock from the Eocene-Miocene Strophodieilus stem of Central Patagonia.